Dampak Penerimaan SHU Terhadap Simpan Pinjam di Koperasi - Khusmasari, Jihan; kusmayati, nindya kartika; Suwangsih, Iwang; Kurniawan, Taufik (Universitas Kadiri, 2023)
Investment Funds and Beneficial Credit are business acts that collect and deliver assets to individuals with low incomes, where the motivation behind the assistance is to advance the well-being of its members. This study aims to find out how the remaining operating income affects cooperative savings and loans. This experiment was conducted on several samples totaling 33 correspondents. This study used a quantitative approach with several sample questionnaires. The results of this study were declared valid and reliable, not or free of multicollinearity, and free of heteroscedasticity. A simple linear regression model was obtained by testing 1 (one) independent variable on the dependent variable Y = 11.537 + 0.710 X1 + e, a straight linear regression model was built. From the t test it is known that cooperative acceptance of SHU (X) has a significant and positive effect on Savings and Loans (Y). To increase the welfare of members and the remaining results of operations, cooperatives need to provide loans to members with greater efficiency.